ANALYSIS OF THE CAPABILITIES OF PORTABLE MINE-HUNTING EQUIPMENT OF THE AUXILIARY MINE COUNTERMEASURE DIVISION TO SUPPORT THE SUCCESS OF AMPHIBIOUS ASSAULTS - Priyanto Widodo; Benny Sukandari; Pebrianto Eko Nugroho (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
Revolution in Military Affair (RMA) has encouraged technological developments in the field of mine warfare. Technological developments in the field of mine warfare have produced smart littoral mines, in which a threat that can thwart the implementation of amphibious assaults. This study tries to analyze the Auxiliary Mine Counter Measure (MCM) Division portable mine-hunting equipment capabilities to support the success of amphibious assaults. This study uses the Measurement of Effectiveness (MoE) and the Analytical Hierarchy Process (AHP) methods to measure capabilities and determine priorities for increasing the capability of portable mine-hunting equipment to support amphibious attack support. As a result, the equipment that rushes portable mines is an increase in support for amphibious assaults because it is incompatible with existing technological developments. To be able to support the spirit of the invasion, it is necessary to procure new equipment designed by following latest developments in mine warfare technology.